Perkembangan Metode Pedagogi Pendidikan Agama Kristen Di Indonesia dan Maknanya Di Era Digital - Tirsa Anggreini Sambul; Addy Purnomo Lado; Sanga Harapan (KAPATA: Jurnal Teologi dan Pendidikan Kristen, 2021)
The pedagogy method plays a significant role in the learning process to achieve the predetermined purpose of learning. The methods of Christian pedagogical education should be present by every teacher, teacher at the school, a parent at home, or shepherd or builder in the church. However, the authors have unearthed several facts that teachers have not fully understood pedagogy's methods, particularly in Christian religious education. The authors still find that the educators lack creativity in teaching learners. In addition, the writer has discovered that some teachers are less familiar with the development of the pedagogical method in Christian religious education. Thus the writers have found it necessary to study the ways of Christian education pedagogical in the light of the history of Christian religious education in Indonesia and its significance for the practice of Christian religious education in the digital age. It is hoped that the study will help teachers learn the pedagogical methods of the history of Christian education and improve the digital age's academic ability to support learners in learning Christian religious education both in schools, in churches, and families.AbstrakMetode pedagogi sangat berperan penting dalam proses pembelajaran guna mencapai tujuan pembelajaran yang sudah ditentukan sebelumnya. Metode pedagogi Pendidikan Agama Kristen seharusnya dimiliki oleh setiap pengajar baik guru di sekolah, orang tua di rumah, maupun gembala atau pembina di gereja. namun, penulis menemukan beberapa fakta yang menunjukkan bahwa para guru belum sepenuhnya memahami metode pedagogi khususnya di dalam Pendidikan Agama Kristen. Penulis masih menemukan bahwa kurangnya kreatifitas para pendidik dalam mengajar peserta didik. Selain itu, penulis juga menemukan fakta bahwa ada beberapa guru kurang memahami sejarah perkembangan metode pedagogi dalam pendidikan Agama Kristen. Oleh karena itu penulis merasa perlu untuk meneliti tentang metode pedagogi Pendidikan Agama Kristen dilihat dari perkembangan sejarah Pendidikan Agama Kristen di Indonesia serta maknanya bagi praktek Pendidikan Agama Kristen di Era Digital. Penelitian ini diharapkan dapat membantu para pengajar untuk bisa belajar metode pedagogi dari perkembangan sejarah Pendidikan Agama Kristen serta dapat mengembangkan kemampuan mendidik di era digital guna mendukung para peserta didik dalam belajar pendidikan agama Kristen baik di sekolah, gereja dan keluarga.